The role of attention in processing morphologically complex spoken words: an EEG/MEG study - Leminen, Alina; Lehtonen, Minna; Leminen, Miika; Nevalainen, Päivi; Mäkelä, Jyrki; Kujala, Teija (Frontiers in Human Neuroscience, 2013)
This study determined to what extent morphological processing of spoken inflected and derived words is attention-independent. To answer these questions EEG and MEG responses were recorded from healthy participants while they were presented with spoken Finnish inflected, derived, and monomorphemic words. In the non-attended task, the participants were instructed to ignore the incoming auditory stimuli and concentrate on the silent cartoon. In the attended task, previously reported by Leminen et al. (Frontiers in Human Neuroscience, 2011, 5:66), the participants were to judge the acceptability of each stimulus. Importantly, EEG and MEG responses were time-locked to the onset of critical information (suffix onset for the complex words and uniqueness point for the monomorphemic words). Early after the critical point, word type did not interact with task: In both attended and non-attended tasks, the ERPs showed larger negativity to derived than inflected or monomorphemic words ~100 ms after the critical point. MEG source waveforms showed a similar pattern. Later than 100 ms after the critical point, there were no differences between word types in the non-attended task either in the ERP or source modeling data. However, in the attended task inflected words elicited larger left-lateralized negativity and source amplitudes than other words ~200 ms after the critical point. The results suggest different brain representations for derived and inflected words. The early activation after the critical point was elicited both in the non-attended and attended tasks. As this stage of word recognition was not modulated by attention, it can be concluded to reflect an automatic mapping of incoming acoustic information onto stored representations. In contrast, the later differences between word types in the attended task were not observed in the non-attended task. This indicates that later compositional processes at the (morpho)syntactic-semantic level require focused attention.